Customs and traditions of China from the third century AH / ninth century AD until the end of the sixth century AH / twelfth century A.D. - Al-Alaywi, Ahmed Nashmi Jiyad; Al-Saadi, Ikrima Kamel (Al-Adab Journal, 2020)
The social aspect in the countries of China was considered an important aspect that attracted the attention of Arab and Muslim travelers and geographers during the Middle Ages. They pointed to many aspects of social life in these countries, including clothing, marriage, holidays, and so on in detail, so this study sought to identify social life in The country of China, the third century AH / ninth century AD, to the end of the sixth century AH / twelfth century A.D. through books of trips and geography, and what was mentioned by travelers and geographers about the social aspect of this country in that period whose trips were limited to the countries of China, for example For Suleiman the merchant, the Serafi, and Barzak bin Shahriar, and the topic is considered an important topic to shed light on the lives of the peoples and tribes of the countries of China and the knowledge of organizing their affairs and ways of living in addition to knowing some common aspects between this country and neighboring countries such as India.